Synthesis of Au-Fe Containing Hybrid Heterostructures via Seeded Growth Approaches - Shaghraf (Curtin University, 2019)
This research work revolves around the formation of gold-iron (Au-Fe) based hybrid nanomaterials (HNMs) by seeded-growth method. By carefully selecting experimental conditions and constituent materials, high order hybrid heterostructures were constructed with novel combination and morphologies. Primarily, two and three component containing HNMs of gold-pyrrhotite (Au-Fe7S8), nickel (Ni) and cobalt (Co) based (Au-Fe7S8/NiS and Au-Fe7S8/CoS1. 035) NPLs were synthesized. By simplifying existing methods a multifunctional kinked trimer of iron oxide-gold-cadmium sulfide (Fe3O4-Au-CdS) was also reported.